HUBUNGAN PENGETAHUAN DAN DUKUNGAN KELUARGA TERHADAP KEPATUHAN MINUM OBAT HIPERTENSI - Febriana Febriana; Desmon Wirawati; Lena Adha (PT Nuansa Fajar Cemerlang, 2026)
Hypertension remains a major public health problem in Indonesia, with a high prevalence (approximately 34% in 2018 and 34.11% in 2023), placing Indonesia fifth worldwide. This increase is influenced by unhealthy lifestyles, lack of awareness of early detection, and hypertension being a major risk factor for other life-threatening diseases such as stroke, heart disease, and kidney failure, particularly among the productive-age population. Methods: This study employed a quantitative design with a cross-sectional approach. A total of 352 respondents were selected using purposive sampling. Research instruments included questionnaires on knowledge, family support, and adherence to antihypertensive medication, which had undergone validity and reliability testing. Data analysis was conducted using the Chi-Square test. Results and Discussion: The majority of respondents had good knowledge but were not adherent to antihypertensive medication. Most respondents with low family support were also classified as non-adherent. Statistical analysis showed a significant relationship between family support and medication adherence among patients with hypertension (p < 0.05). However, no significant relationship was found between knowledge and medication adherence (p > 0.05). Suggestion: The results indicate that although respondents generally had good knowledge, adherence to antihypertensive medication was still predominantly low. Family support showed a significant association with medication adherence among patients with hypertension. These findings suggest that enhancing instrumental support—such as reminding patients of medication schedules, facilitating access to healthcare services, and accompanying patients during treatment—contributes substantially to improving medication adherence.